Influencers e INDECOPI: el problema de la solución a la publicidad encubierta - Díaz-Valdez, Alejandro (2021)
The arrival of influencers has generated a new type of advertising, which is why the Peruvian National Institute for the Defense of Competition and Intellectual Property-INDECOPI presented the “Guide on Digital Advertising and recommendations for Influencers [Project]”. It offers guidelines that influencers should follow when posting advertisement in their social media and, in that way, not fail to comply with, among others, the Repression of Unfair Competition Law. This article aims to present to the reader the main problems that arise from the reading of the mentioned project guide and the difficulties its current wording poses for its execution.